2014
DOI: 10.1111/pbr.12152
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mapping of black rot resistance locusXca1boon chromosome 3 inIndian cauliflower (Brassica oleraceavar.botrytisL.)

Abstract: Black rot is the most devastating disease of cauliflower worldwide causing severe damage to crop. The identification of markers linked to loci that control resistance can facilitate selection of plants for breeding programmes. In the present investigation, F 2 population derived from a cross between 'Pusa Himjyoti', a susceptible genotype, and 'BR-161', a resistant genotype, was phenotyped by artificial inoculation using Xcc race 1. Segregation analysis of F 2 progeny indicated that a single dominant locus gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…However, the strong resistance source for Xcc race 4 was reported to be originated from A genome while resistance to both races 1 and 4 from B genome, and B. juncea (AB genome) was the most resistant species to races 1 and 4 . To date, several QTLs for black rot resistance have been described in B. oleracea and other B. species (Camargo et al 1995;Cheng et al 2009;Kifuji et al 2013;Izzah et al 2014;Saha et al 2014;Lee et al 2015;Sharma et al 2016). In this study, five reported SSR markers showed polymorphism in banding pattern for R and S lines of the tested cabbage lines.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…However, the strong resistance source for Xcc race 4 was reported to be originated from A genome while resistance to both races 1 and 4 from B genome, and B. juncea (AB genome) was the most resistant species to races 1 and 4 . To date, several QTLs for black rot resistance have been described in B. oleracea and other B. species (Camargo et al 1995;Cheng et al 2009;Kifuji et al 2013;Izzah et al 2014;Saha et al 2014;Lee et al 2015;Sharma et al 2016). In this study, five reported SSR markers showed polymorphism in banding pattern for R and S lines of the tested cabbage lines.…”
Section: Discussionmentioning
confidence: 63%
“…Kifuji et al (2013) reported a QTL for black rot resistance using 161 EST-SNP markers and found that QTL-1 located on LG C02 is the major QTL in cabbage. A major black rot resistance locus called Xca1bo has been mapped on Chromosome 03 in Indian cauliflower (Saha et al 2014). Lee et al (2015) reported a genetic linkage map where they identified four QTLs such as BRQTL-C1_1 and BRQTL-C1_2 on LG C01, BRQTL-C3 on LG C03 and BRQTL-C6 on LG 06.…”
Section: Introductionmentioning
confidence: 99%
“…In the latter case, fungal pathogens are known to quickly develop resistance to most chemicals and the use of fungicides is generally perceived as negative for human health and the environment ( Van de Wouw et al, 2014 ; Balint-Kurti and Holland, 2015 ). For this reason, genetic approaches are considered safer and more durable, and considerable efforts are deployed toward the identification and introgression of resistance genes into plant material ( Channamallikarjuna et al, 2010 ; Raman et al, 2012 ; Singh et al, 2012 ; Saha et al, 2014 ). However, the use of a single source of resistance also brings tremendous selection pressure on the pathogen, and the resistance often breaks down quite rapidly ( Kutcher et al, 2013 ; Van de Wouw et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tuno et al 42 analyzed BR resistance QTLs and the major QTL XccBo(Reiho)2 was detected on C8. Saha et al 43 mapped the Xcc race 1 resistance gene Xca1bo in the cauliflower line BR-161 within a 1.6 cM interval. Sharma et al 44 first developed a B. carinata F 2 mapping population and mapped the BR race 1 resistance locus Xca1bc to a 6.6 cM interval.…”
Section: Black Rotmentioning
confidence: 99%